(untitled) (Nexus International Journal of Science and Education, 2024)
The study aimed to investigate the influence of video gaming on students’ English proficiency. In this study, the researcher selected 155 junior high school students in Governor Generoso South District in Davao Oriental as the respondents of the study. A stratified random sampling technique was utilized in the selection of the respondents. A non-experimental quantitative research design using a descriptive-correlational method was employed. The data collected were subjected to the following statistical tools: Mean, Pearson Moment Product Correlation, and linear regression analysis. Findings revealed that video gaming was described as moderately extensive, while students’ English proficiency in Governor Generoso South District, Davao Oriental, was rated as extensive. Further, correlation analysis demonstrated a significant relationship between video gaming and students’ English proficiency in Governor Generoso South District, Davao Oriental. Regression analysis proved that video gaming, in terms of engagement and motivation, active learning, and customized learning, significantly influenced the students’ English proficiency in Governor Generoso South District, Davao Oriental. Thus, DepEd should also allocate resources to schools to invest in technology and educational games that promote English proficiency.